Mass immigrations in the 21st century. Case of Belgium and the Netherlands - Żelichowski, Ryszard (European Spatial Research and Policy, 2019)
The uncontrolled wave of immigrants to the European Union countries, which reached its peak in 2015, challenged not only the well-established system of asylum policies in the Member States but also revealed the fundamental differences among them concerning the so-called “immigration issue”. The article focuses on the mechanisms and institutions which evolved during the different waves of immigrants in Belgium and the Netherlands. It also looks for an answer to the question: is mass immigration to Europe a threat or an opportunity? Depending on one’s attitude to the topic, the answer may be positive or negative.